Dural Venous Sinus Thrombosis and Pulmonary Embolism Following Immunoglobulin Treatment in Pediatric Patient With Immune Thrombocytopenic Purpura. Issue 8 (November 2017) - Park, Kyung Mi; Yang, Eu Jeen; Lim, Young Tak
Abstract : Intravenous immunoglobulin (IVIG) is a widely used agent as the first choice of treatment of immune thrombocytopenic purpura (ITP). IVIG has several side effects, but it is a relatively safe treatment. Life-threatening thrombosis has been reported in adults and rarely in children. We report a case of a 14-year-old boy with dural venous sinus thrombosis and pulmonary embolism after treatment with IVIG for ITP. The patient was treated with low–molecular-weight heparin followed by warfarin and the symptoms were recovered. If a patient with ITP shows mental change or respiratory difficulty, we should consider thrombosis as well as hemorrhage.